Drama Elements Through The Application Of Cooperative Integratedreading And Composition (Circ) Students In Grade VII-A SMP Negeri 1 Gunungsitoli Idanoi - Natal Kristiani Gea (EDUCATION JOURNAL OF INDONESIA, 2020)
This research is supported by the lack of basic abilities of students in reading and understanding drama texts. This is because students are less able to understand the flow, background, mandate and language style contained in the drama. To overcome this, the authors applied the CIRC learning model with the aim that students were able to understand the flow, background, mandate and language style contained in the drama. This research was conducted at SMP Negeri 1 Gunungsitoli Idanoi with the research subjects of class VIII-A students in the 2018/2019 Learning Year which totaled 27 people. The research method used was classroom action research (PTK). Based on the research results obtained (1) the average student learning outcomes in the first cycle was 63.52 and in the second cycle increased by an average of 78.89. (2) completeness of student learning in the first cycle 59.26%, an increase in the second cycle to 92.59%. Therefore, it can be concluded that the CIRC learning model can improve students' ability to understand the intrinsic elements of drama, because the CIRC learning model makes students responsible for group assignments and in groups students are also able to issue ideas to understand a concept and complete assignments.